2011
DOI: 10.1262/jrd.10-122h
|View full text |Cite
|
Sign up to set email alerts
|

Analyses of the Regulatory Mechanism of Porcine WEE1B: The Phosphorylation Sites of Porcine WEE1B and Mouse WEE1B Are Different

Abstract: Abstract. WEE1B, an oocyte-specific kinase, phosphorylates the CDC2 inhibitory site and maintains the meiotic arrest of oocytes at the first meiotic prophase in several mammalian species. However, the molecular mechanisms controlling WEE1B activity have not been fully examined in species other than mice. In the present study, we analyzed the regulation mechanisms of porcine WEE1B (pWEE1B), focusing on the cAMP-dependent protein kinase (PKA) phosphorylation site and intracellular localization. As the PKA phosph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
1
3
0
Order By: Relevance
“…These results are similar to those found in the previous report where WEE1B suppression was used instead of PKA inhibition and GVBD rates were examined in CDC2-overexpressed and/or WEE1B-suppressed GOs [11]. Because PKA phosphorylates and activates WEE1B [2][3][4][5], the effect of continuous PKA activation in GOs could be mediated by continuous WEE1B activation and inhibition of CDC2 kinase by activated WEE1B. These facts indicate that CDC2 activity is inhibited both quantitatively and qualitatively rather than by either of mechanism alone, implying that a double-pronged mechanism is used by mammalian GOs in preventing an unexpected activation of CDC2.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…These results are similar to those found in the previous report where WEE1B suppression was used instead of PKA inhibition and GVBD rates were examined in CDC2-overexpressed and/or WEE1B-suppressed GOs [11]. Because PKA phosphorylates and activates WEE1B [2][3][4][5], the effect of continuous PKA activation in GOs could be mediated by continuous WEE1B activation and inhibition of CDC2 kinase by activated WEE1B. These facts indicate that CDC2 activity is inhibited both quantitatively and qualitatively rather than by either of mechanism alone, implying that a double-pronged mechanism is used by mammalian GOs in preventing an unexpected activation of CDC2.…”
Section: Discussionsupporting
confidence: 90%
“…The resumption of meiosis requires elevation of CDC2 kinase activity, although this elevation is inhibited in ovarian follicles by a high intraoocyte cAMP level and resulting high cAMPdependent protein-kinase (PKA) activity [1]. In meioticarrested mouse and pig oocytes, it has been reported that active PKA phosphorylates and activates WEE1B, an oocytespecific member of the WEE1 kinase family, and that the active WEE1B phosphorylates inhibitory phosphorylation sites of CDC2 in order to maintain its low activity [2][3][4]. The cAMP level and PKA activity in full-grown oocytes (FGOs) is decreased drastically by hormonal stimulation or isolation from follicles, resulting in inactivation of WEE1B and subsequent CDC2 activation, which induces meiotic resumption [5].…”
Section: Introductionmentioning
confidence: 99%
“…PKA is important in regulating the cell cycle progression of eukaryotic organisms. A study by Shimaoka et al suggested that continuous high PKA activity is a primary cause of the meiotic incompetence of pig-growing oocytes, and that this PKA activity is, not only caused by an insufficient expression level of PKA subunits, but may be attributed to more complex spatial-temporal regulation mechanisms (45). Our studies have demonstrated that PKA negatively regulates cell cycle progression in one-cell stage mouse embryos by inhibiting MPF (46) and CDC25B acts as a direct substrate of PKA (27).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, although UBE2 overexpression showed a decrease in the CCNB level, the oocytes were able to reach MI, similar to the controls. In the initiation of porcine oocyte maturation, the activation of MPF is attributed to the dephosphorylation of pre-MPF, and the initiation of germinal vesicle breakdown (GVBD) can take place even with low MPF activity [ 23 , 32 ]. It was also reported in mice that inhibition or overexpression of UBE2 did not have an impact on the meiotic resumption of oocytes [ 19 ].…”
Section: Discussionmentioning
confidence: 99%